Composite iron oxide thin film and powder, and methods for producing the same

JP2025036402APending Publication Date: 2025-03-14RESEARCH INSTITUTE FOR ELECTROMAGNETIC MATERIALS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024152333
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-04
Filing Date
2024-09-04
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0023】 Si、Zr、MnおよびCrの群からなる少なくとも1種の元素が所定の量添加された、本発明に係る複合鉄酸化物薄膜および粉末によれば、耐酸化性の向上がさらに図られているとともに磁化または透光性の向上が図られる。このため、本発明の複合鉄酸化物薄膜および粉末は、耐酸化性の向上が図られたマグへマイトの特徴を有する材料または光触媒としての材料として好適に利用可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036402000001_ABST
    Figure 2025036402000001_ABST
Patent Text Reader

Abstract

To provide a composite iron oxide thin film with improved oxidation resistance, and a production method therefor.SOLUTION: The present invention provides a composite iron oxide thin film comprising a first iron oxide layer X1 and a second iron oxide layer X2 as a surface layer that forms a heterostructure with the first iron oxide layer X1. The first iron oxide layer X1 is represented by the composition formula Fe1-x-yLxOy (where L is at least one element selected from the group consisting of Si, Zr, Mn, and Cr), and is composed of a maghemite crystal phase. The second iron oxide layer X2 is represented by the composition formula Fe1-u-vLuOv, and is composed of a hematite crystal phase.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to composite iron oxide thin films and powders that form heterostructures, and to methods for producing the same. [Background technology]

[0002] As iron oxide oxidizes, it turns into wustite (Fe 1-x O) to magnetite (Fe 3 O 4 ), maghemite (γ-Fe 2 O 3 ), and finally hematite (α-Fe 2 O 3 ), which results in a phase transition to semimetallic, ferrimagnetic and semiconducting properties. 3 O 4 is the Fe atom at the octahedral B site. 2+ and Fe in both the tetrahedral A site and the octahedral B site. 3+ This situation occurs when the electrons move from Fe to Fe at temperatures above 120 K. 2+ and Fe 3+ Since the temperature transition occurs between 0 and 850 K (Verwey transition), the electrical resistivity is relatively low (see, for example, Non-Patent Document 1), and the ferrimagnetic behavior exists up to 850 K (see, for example, Non-Patent Document 2). These properties have potential applications in spintronics devices (see, for example, Non-Patent Document 3), gas sensors (see, for example, Non-Patent Document 4), resistive random access memories (see, for example, Non-Patent Document 5), and the like.

[0003] Fe 3 O 4 In order to maintain the performance of devices or elements containing Fe and to expand their use in other applications, 3 O 4 It is necessary to increase the transition temperature of powder Fe 3 O 4 The phase transition depends on the heat treatment temperature and the crystal size (see, for example, Non-Patent Documents 6 to 17). When the temperature exceeds 493 K, crystals with a size of 300 nm or less are formed in the γ-Fe 2 O3 (For example, see Non-Patent Document 11). This occurs because the activation energy of the phase transition decreases as the grain size decreases (For example, see Non-Patent Document 14). When at least one of Mn, Co, Ni, Zn, Cu, Al, and V is added, the transition temperature increases from 773 K to 923 K. Fe 3 O 4 To protect the core from oxidation, SnO 2 Alternative techniques for iron oxide nanoparticles have been proposed, such as forming core-shell structures with shells of iron oxide nanoparticles (see, for example, Non-Patent Document 18) and carbon phosphate materials (see, for example, Non-Patent Document 19). When formed as a thin film, the undoped Fe 3 O 4 γ-Fe 2 O 3 (For example, see Non-Patent Document 20) but with metal doping Fe 3 O 4 It is unclear how to make the thin film oxidation resistant.

[0004] Fe 3 O 4 Single-phase Fe produced using radio frequency (RF) sputtering with a metal tip on the target 3 O 4 In addition to the method of producing the membrane, the ceramic Fe 3 O 4 Target is Fe 3 O 4 and α-Fe 2 O 3 It has been reported that a phase mixture is formed (see, for example, Patent Document 1 and Non-Patent Documents 21 and 22). 3 O 4 The magnetization of the thin films was found to be maximized at relatively low metal concentrations.

[0005] The present inventors have also disclosed a composite iron oxide thin film having improved oxidation resistance and a method for producing the same, in which one or more elements selected from the group consisting of Mo, W, and Mg are added to the maghemite crystal phase, or Ge is added to the magnetite crystal phase, providing a magnetic material with oxidation resistance (Patent Document 2). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 5389370 [Patent Document 2] Patent No. 7153555 [Non-patent literature]

[0007] [Non-Patent Document 1] E, J. Verwey, PW Haayman, and FC Romeijn, J. Chem. Phys. 15 (1947) 181. [Non-Patent Document 2] GA Samara, AA Giardini, Phys. Rev. 186 (1969)578. [Non-Patent Document 3] KI Aoshima and SX Wang, J. Appl. Phys. 93 (2003) 7954. [Non-Patent Document 4] M. Aronniemi, J. Saino and J. Lahtinen, Thin Solid Films 516 (2008) 6110. [Non-Patent Document 5] K. Kinoshita, T. Tamura, M. Aoki, Y. Sugiyama and H. Tanaka, Appl.Phys. Lett. 89 (2006) 103509. [Non-Patent Document 6] M. S. Cresser and N. T. Livesev, Analyst 109 (1984) 219.

Non - Patent Document 7

Non - Patent Document 8

Non - Patent Document 9

Non - Patent Document 10

Non - Patent Document 11

Non - Patent Document 12

Non - Patent Document 13

Non - Patent Document 14

Non - Patent Document 15

[0008] The composite iron oxide thin film and the method for producing the composite iron oxide thin film disclosed in Patent Document 2 improve the oxidation resistance. On the other hand, the composite iron oxide thin film having the characteristics of maghemite disclosed in Patent Document 2 has Mo added thereto to improve the oxidation resistance, but has low magnetization and light transmittance and lacks practicality.

[0009] An object of the present invention is to provide a composite iron oxide thin film and a method for producing the same, in which the oxidation resistance is further improved, and the magnetization or light transmittance is improved. Another object of the composite iron oxide thin film of the present invention is to provide a material having the characteristics of magnetite with improved oxidation resistance or a material as a photocatalyst.

[0010] Powder can increase the surface area per volume compared to the thin film form and is useful. A further object of the present invention is to provide a composite iron oxide powder in which the oxidation resistance is further improved and the magnetization or light transmittance is improved.

Means for Solving the Problems

[0011] In order to solve the above problems, the composite iron oxide thin film and the method for producing the composite iron oxide thin film of the present invention are characterized by having the following invention specific matters.

[0012] The composite iron oxide thin film of the present invention Composition formula Fe 1-x-y Si x O y (However, 0 < x ≦ 0.10, 0.57 ≦ y ≦ 0.61, and 0.29 ≦ 1 - (x + y) ≦ 0.41.) represented by, and a first iron oxide layer composed of a maghemite crystal phase, Composition formula Fe 1-u-v Si u O v (However, 0 ≦ u ≦ 0.01, 0.59 ≦ v ≦ 0.61, and 0.37 ≦ 1 - (u + v) ≦ 0.41.) represented by, and a second iron oxide layer as a surface layer constituting a heterostructure with the first iron oxide layer, which is composed of a hematite crystal phase, and is characterized by comprising.

[0013] The composite iron oxide thin film of the present invention Composition formula Fe 1-x-y Zr x O y(However, it is represented by 0 < x ≤ 0.10, 0.57 ≤ y ≤ 0.61, and 0.29 ≤ 1 - (x + y) ≤ 0.41, and a first iron oxide layer composed of a maghemite crystal phase and Composition formula Fe 1-u-v Zr u O v (However, it is represented by 0 ≤ u ≤ 0.01, 0.59 ≤ v ≤ 0.61, and 0.37 ≤ 1 - (u + v) ≤ 0.41, and a second iron oxide layer as a surface layer constituting a heterostructure with the first iron oxide layer, which is composed of a hematite crystal phase, and is characterized by comprising the same.

[0014] The composite iron oxide thin film of the present invention Composition formula Fe 1-x-y Mn x O y (However, it is represented by 0 < x ≤ 0.22, 0.57 ≤ y ≤ 0.61, and 0.29 ≤ 1 - (x + y) ≤ 0.41, and a first iron oxide layer composed of a maghemite crystal phase and Composition formula Fe 1-u-v Mn u O v (However, it is represented by 0 ≤ u ≤ 0.01, 0.59 ≤ v ≤ 0.61, and 0.37 ≤ 1 - (u + v) ≤ 0.41), and a second iron oxide layer as a surface layer constituting a heterostructure with the first iron oxide layer, which is composed of a hematite crystal phase, and is characterized by comprising the same.

[0015] The composite iron oxide thin film of the present invention Composition formula Fe 1-x-y Cr x O y (However, it is represented by 0 < x ≤ 0.10, 0.57 ≤ y ≤ 0.61, and 0.29 ≤ 1 - (x + y) ≤ 0.41, and a first iron oxide layer composed of a maghemite crystal phase and Composition formula Fe 1-u-v Cr u O v(However, 0 ≦ u ≦ 0.01, 0.59 ≦ v ≦ 0.61, and 0.37 ≦ 1 - (u + v) ≦ 0.41.), and is composed of a hematite crystal phase, a second iron oxide layer as a surface layer constituting a heterostructure with the first iron oxide layer, and is characterized by comprising the same.

[0016] The method for manufacturing a composite iron oxide thin film of the present invention is Using Fe as a target material 3 O 4 By high-frequency sputtering using a composite target in which a Si chip is disposed on the target, a thin film represented by the composition formula Fe 1-a-b Si a O b (However, 0 < a ≦ 0.1, 0.48 ≦ b ≦ 0.61, and 0.32 ≦ 1 - (a + b) ≦ 0.43.), and is composed of a magnetite crystal phase, and a step of producing a thin film; By heat-treating the thin film at a predetermined temperature within the temperature range of 573 K to 873 K (300 °C to 600 °C) for a predetermined time within the time range of 10 minutes to 256 days, as the surface layer of the thin film, a composition formula Fe 1-u-v Si u O v (However, 0 ≦ u ≦ 0.01, 0.59 ≦ v ≦ 0.61, and 0.37 ≦ 1 - (u + v) ≦ 0.41.), and is composed of a hematite crystal phase, and a surface layer is produced, and as the inner layer of the thin film, a composition formula Fe 1-x-y Si x O y (However, 0 < x ≦ 0.10, 0.57 ≦ y ≦ 0.61, and 0.29 ≦ 1 - (x + y) ≦ 0.41.), and is composed of a maghemite crystal phase, and a step of creating an inner layer; and is characterized by including the same.

[0017] The method for manufacturing a composite iron oxide thin film of the present invention is Using Fe as a target material 3 O 4 By high-frequency sputtering using a composite target in which a Zr chip is disposed on the target, a composition formula Fe 1-a-b Zr a Ob (However, 0 < a ≤ 0.1, 0.48 ≤ b ≤ 0.61, and 0.32 ≤ 1 - (a + b) ≤ 0.43.), and a step of manufacturing a thin film composed of a magnetite crystal phase, By heat-treating the thin film at a predetermined temperature within the temperature range of 573K to 873K (300°C to 600°C) for a predetermined time within the time range of 10 minutes to 256 days, as the surface layer of the thin film, the composition formula is Fe 1-u-v Zr u O v (However, 0 ≤ u ≤ 0.01, 0.59 ≤ v ≤ 0.61, and 0.37 ≤ 1 - (u + v) ≤ 0.41.), and a surface layer composed of a hematite crystal phase is manufactured, and as the inner layer of the thin film, the composition formula is Fe 1-x-y Zr x O y (However, 0 < x ≤ 0.10, 0.57 ≤ y ≤ 0.61, and 0.29 ≤ 1 - (x + y) ≤ 0.41.), and a step of creating an inner layer composed of a maghemite crystal phase is included, and it is characterized by including this.

[0018] The method for manufacturing a composite iron oxide thin film of the present invention is Using a composite target with Mn chips arranged on a target as a target material, by high-frequency sputtering method, the composition formula is Fe 3 O 4 (However, 0 < a ≤ 0.22, 0.48 ≤ b ≤ 0.61, and 0.32 ≤ 1 - (a + b) ≤ 0.43.), and a step of manufacturing a thin film composed of a magnetite crystal phase, 1-a-b Mn a O b (However, 0 < a ≤ 0.22, 0.48 ≤ b ≤ 0.61, and 0.32 ≤ 1 - (a + b) ≤ 0.43.), and a step of manufacturing a thin film composed of a magnetite crystal phase, By heat-treating the thin film at a predetermined temperature within the temperature range of 573K to 873K (300°C to 600°C) for a predetermined time within the time range of 10 minutes to 256 days, as the surface layer of the thin film, the composition formula is Fe 1-u-v Mn u O v(However, it is represented by 0 ≦ u ≦ 0.01, 0.59 ≦ v ≦ 0.61, and 0.37 ≦ 1 - (u + v) ≦ 0.41), and a surface layer composed of a hematite crystal phase is formed. As the inner layer of the thin film, the composition formula is Fe 1-x-y Mn x O y (However, it is represented by 0 < x ≦ 0.22, 0.57 ≦ y ≦ 0.61, and 0.29 ≦ 1 - (x + y) ≦ 0.41), and a step of creating an inner layer composed of a maghemite crystal phase is included, and is characterized by this.

[0019] The method for manufacturing a composite iron oxide thin film of the present invention is Using a composite target in which a Cr chip is arranged on a target material Fe 3 O 4 By high-frequency sputtering method, a thin film represented by the composition formula Fe 1-a-b Cr a O b (However, it is represented by 0 < a ≦ 0.1, 0.48 ≦ b ≦ 0.61, and 0.32 ≦ 1 - (a + b) ≦ 0.43), and a step of forming a thin film composed of a magnetite crystal phase is included, By heat-treating the thin film at a predetermined temperature within the temperature range of 573 K to 873 K (300 °C to 600 °C) for a predetermined time within the time range of 10 minutes to 256 days, as the surface layer of the thin film, the composition formula is Fe 1-u-v Cr u O v (However, it is represented by 0 ≦ u ≦ 0.01, 0.59 ≦ v ≦ 0.61, and 0.37 ≦ 1 - (u + v) ≦ 0.41), and a surface layer composed of a hematite crystal phase is formed. As the inner layer of the thin film, the composition formula is Fe 1-x-y Cr x O y (However, it is represented by 0 < x ≦ 0.10, 0.57 ≦ y ≦ 0.61, and 0.29 ≦ 1 - (x + y) ≦ 0.41), and a step of creating an inner layer composed of a maghemite crystal phase is included, and is characterized by this.

[0020] Also, in order to solve the above problems, the composite iron oxide powder and its manufacturing method of the present invention are characterized by having the following invention specific matters.

[0021] The composite iron oxide powder of the present invention is with the composition formula Fe 1-x-y Si x O y (However, 0 < x ≤ 0.10, 0.57 ≤ y ≤ 0.61, and 0.29 ≤ 1 - (x + y) ≤ 0.41.) and a maghemite crystal phase represented by with the composition formula Fe 1-u-v Si u O v (However, 0 ≤ u ≤ 0.01, 0.59 ≤ v ≤ 0.61, and 0.37 ≤ 1 - (u + v) ≤ 0.41.) and a hematite crystal phase represented by, a composite iron oxide powder composed of the surface layer portion of the composite iron oxide powder is composed of the hematite crystal phase, and the interior of the composite iron oxide powder that is at least partially covered by the surface layer portion is composed of the maghemite crystal phase.

[0022] The manufacturing method of the composite iron oxide powder of the present invention is with the composition formula Fe 1-x-y Si x O y (However, 0 < x ≤ 0.10, 0.57 ≤ y ≤ 0.61, and 0.29 ≤ 1 - (x + y) ≤ 0.41.) and a maghemite crystal phase represented by, and a composition formula Fe 1-u-v Si u O v (However, 0 ≤ u ≤ 0.01, 0.59 ≤ v ≤ 0.61, and 0.37 ≤ 1 - (u + v) ≤ 0.41.) and a hematite crystal phase represented by, a method for manufacturing a composite iron oxide powder composed of In a non-oxidizing atmosphere or in a vacuum, at a temperature within the temperature range of 1073 to 1473 K, over a time within the time range of 4 to 48 hours, α-Fe 2 O 3 , α-Fe and SiO 2 heat-treating a compact composed of a mixed powder of and pulverizing the heat-treated molded body. Effect of the Invention

[0023] The composite iron oxide thin film and powder of the present invention, to which at least one element selected from the group consisting of Si, Zr, Mn, and Cr is added in a predetermined amount, further improves the oxidation resistance and also improves the magnetization or light transmittance. Therefore, the composite iron oxide thin film and powder of the present invention can be suitably used as a material having the characteristics of maghemite with improved oxidation resistance or as a material for use as a photocatalyst. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is a diagram illustrating the configuration of a composite iron oxide according to one embodiment of the present invention. [Diagram 2] 3 is a ternary phase diagram of the iron oxide thin film according to the present invention. [Figure 3A] FIG. 1 is an explanatory diagram of the correlation between the amount of Si added and the X-ray diffraction pattern of an iron oxide thin film before heat treatment. [Figure 3B] FIG. 1 is a graph showing the correlation between the amount of Si added and the magnetization curve of an iron oxide thin film before heat treatment. [Figure 4A] FIG. 13 is a graph showing the change in magnetization at 10 kOe versus the amount of Si added to an iron oxide thin film before heat treatment. [Figure 4B] This figure shows the XPS spectrum of an iron oxide thin film with a Si addition of 2.8 at.% before heat treatment. [Figure 5A] Correlation of X-ray diffraction patterns of a composite iron oxide thin film after heat treatment at a temperature of 673 K for 256 days. [Figure 5B] Raman spectrum of a composite iron oxide thin film after heat treatment at 673 K for 256 days. [Figure 6A] HAADF-STEM image of a Si-doped complex iron oxide thin film (Si content 2.8 at.%) after heat treatment at 673 K for 256 days. [Figure 6B] STEM-EDX elemental map image of Si-K of Si-doped complex iron oxide thin film (Si content 2.8 at.%) after heat treatment at 673 K for 256 days. [Figure 6C] STEM-EDX elemental map image of OK Si-doped complex iron oxide thin film (Si content 2.8 at.%) after heat treatment at 673 K for 256 days. [Figure 6D] STEM-EDX elemental map image of Fe-K of Si-doped complex iron oxide thin film (Si content 2.8 at.%) after heat treatment at 673 K for 256 days. [Figure 7A] STEM cross-sectional image of a Si-doped complex iron oxide thin film (Si content 2.8 at.%) after heat treatment at 673 K for 256 days. [Figure 7B] Fast Fourier transform analysis image of the surface layer in the image of Figure 7A. [Figure 7C] Fast Fourier transform analysis image of the inner layer in the image of FIG. 7A. [Figure 8A] A graph showing the change in magnetization of a Si-containing complex iron oxide thin film versus heat treatment time in air at 673 K. [Figure 8B] A graph showing the change in magnetization of a Zr-containing complex iron oxide thin film versus heat treatment time in air at 673 K. [Figure 8C] A graph showing the change in magnetization of a Mn-containing complex iron oxide thin film versus heat treatment time in air at 673 K. [Figure 8D] A graph showing the change in magnetization of a Cr-containing complex iron oxide thin film versus heat treatment time in air at 673 K. [Figure 9] A graph showing the change in magnetization of a composite iron oxide thin film versus the amount of Si added after 90 minutes of heat treatment at different temperatures. [Figure 10A] A graph showing the change in magnetization of a composite iron oxide thin film with different amounts of Si added after different heat treatment times in air at 673 K. [Figure 10B]A graph showing the change in magnetization of a composite iron oxide thin film with different amounts of Zr added after different heat treatment times in air at 673 K. [Figure 10C] A graph showing the change in magnetization of a composite iron oxide thin film with different amounts of Mn added, after heat treatment at 673 K in air for different times. [Figure 10D] A graph showing the change in magnetization of a composite iron oxide thin film with different amounts of Cr added, after heat treatment for different times in air at 673K. [Figure 11] FIG. 2 is a graph showing the optical transmission spectra of composite iron oxide thin films in Example 1 and Comparative Example 2, which were subjected to a heat treatment at 673 K for 256 days. [Figure 12] The optical transmission spectra of a composite iron oxide thin film (Si content 2.8 at.%) after 90 minutes of heat treatment in air at different temperatures. [Figure 13A] The optical transmission spectra of a composite iron oxide thin film (Si content 2.8 at.%) after heat treatment at 773 K for different times. [Figure 13B] The optical transmission spectra of a composite iron oxide thin film (Zr content 4.0 at.%) after heat treatment at 673 K for different times. [Figure 13C] Optical transmission spectra of a composite iron oxide thin film (Mn content 8.9 at.%) after heat treatment at 673 K for different times. [Figure 13D] Optical transmission spectra of a composite iron oxide thin film (Mn content 17 at.%) after heat treatment at 673 K for different times. [Figure 13E] The optical transmission spectra of a composite iron oxide thin film (Cr content 4.5 at.%) after heat treatment at 673 K for different times. [Figure 14] FIG. 2 is an explanatory diagram of a method for producing a composite iron oxide powder. [Figure 15] A graph showing the relationship between magnetization and composition x of SixFe3-xO4 powder. [Figure 16] FIG. 1 shows the correlation of X-ray diffraction patterns of composite iron oxide powders. [Figure 17]Figure showing the Raman spectra of the composite iron oxide powder (Si composition ratio = 0.1) before and after heat treatment.

Mode for Carrying Out the Invention

[0025] (Configuration) As one embodiment of the present invention, a composite iron oxide thin film (γ-Fe 2 O 3 / α-Fe 2 O 3 thin film), as schematically shown in FIG. 1, has a first iron oxide layer X1 composed of a maghemite (γ-Fe 2 O 3 ) crystal layer, and a second iron oxide layer X2 as a surface layer composed of a hematite (α-Fe 2 O 3 ) crystal phase. The first iron oxide layer X1 and the second iron oxide layer X2 have a hetero structure. Here, the "hetero structure" means a structure having an interface as if two layers are hetero-junctioned and stacked in an integrally inseparable form. The surface of the second iron oxide layer X2 has low flatness, an irregular roughness curve, and the surface roughness Ra is included in the range of 150 nm or less.

[0026] The first iron oxide layer X1 is represented by the composition formula Fe 1-x-y Si x O y (where 0 < x ≦ 0.10, 0.57 ≦ y ≦ 0.61, and 0.29 ≦ 1-(x + y) ≦ 0.41). Here, the first iron oxide layer X1 is composed of a maghemite crystal phase. The second iron oxide layer X2 is represented by the composition formula Fe 1-u-v Si u O v (where 0 ≦ u ≦ 0.01, 0.59 ≦ v ≦ 0.61, and 0.37 ≦ 1-(u + v) ≦ 0.41).

[0027] Also, x, y, u, and v are not limited to the values described above. The value of x is preferably from 0.001 to 0.1, more preferably from 0.005 to 0.05, and even more preferably from 0.005 to 0.03. The value of y is preferably from 0.57 to 0.61, more preferably from 0.58 to 0.605, and even more preferably from 0.59 to 0.605. The value of u is preferably from 0 to 0.01, more preferably from 0 to 0.005, and even more preferably from 0 to 0.001. The value of v is preferably from 0.59 to 0.61, more preferably from 0.59 to 0.605, and even more preferably from 0.595 to 0.605. Note that since Si is known to dissipate during the heat treatment described below, the value of u theoretically becomes 0 when the heat treatment is sufficiently performed. However, even after sufficient heat treatment, Si may inevitably be present in the second iron oxide layer X2, and its value is on the order of 10 ‐6 of.

[0028] In addition to Si, Mn, Zr, or Cr can be substituted for Si or added together with Si in the first iron oxide layer X1 and the second iron oxide layer X2.

[0029] When Mn is contained in the first iron oxide layer X1 and the second iron oxide layer X2, the first iron oxide layer X1 has the composition formula Fe 1-x-y Mn x O y (However, 0 < x ≤ 0.22, 0.57 ≤ y ≤ 0.61, and 0.29 ≤ 1 - (x + y) ≤ 0.41). Here, the first iron oxide layer X1 is composed of a maghemite crystal phase. The second iron oxide layer X2 has the composition formula Fe 1-u-v Mn u O v (However, 0 ≤ u ≤ 0.01, 0.59 ≤ v ≤ 0.61, and 0.37 ≤ 1 - (u + v) ≤ 0.41).

[0030] In this case, x, y, u, and v are not limited to the values described above. The value of x is preferably from 0.08 to 0.17, more preferably from 0.08 to 0.1, and still more preferably from 0.085 to 0.095. The value of y is preferably from 0.57 to 0.61, more preferably from 0.58 to 0.605, and still more preferably from 0.59 to 0.605. The value of u is preferably from 0 to 0.01, more preferably from 0 to 0.005, and still more preferably from 0 to 0.001. The value of v is preferably from 0.59 to 0.61, more preferably from 0.59 to 0.605, and still more preferably from 0.595 to 0.605. Note that, like Si, Mn is known to dissipate during the heat treatment described later. Therefore, the value of u when the heat treatment is sufficiently performed theoretically becomes 0. However, even after the heat treatment is sufficiently performed, Mn may inevitably exist in the second iron oxide layer X2, and its value is on the order of 10 ‐6 of.

[0031] When Zr is contained in the first iron oxide layer X1 and the second iron oxide layer X2, the first iron oxide layer X1 has the compositional formula Fe 1-x-y Zr x O y (where 0 < x ≤ 0.10, 0.57 ≤ y ≤ 0.61, and 0.29 ≤ 1 - (x + y) ≤ 0.41). Here, the first iron oxide layer X1 is composed of a maghemite crystal phase. The second iron oxide layer X2 has the compositional formula Fe 1-u-v Zr u O v (where 0 ≤ u ≤ 0.01, 0.59 ≤ v ≤ 0.61, and 0.37 ≤ 1 - (u + v) ≤ 0.41).

[0032] Also, x, y, u, and v are not limited to the values described above. The value of x is preferably from 0.001 to 0.1, more preferably from 0.005 to 0.05, and even more preferably from 0.005 to 0.03. The value of y is preferably from 0.57 to 0.61, more preferably from 0.58 to 0.605, and even more preferably from 0.59 to 0.605. The value of u is preferably from 0 to 0.01, more preferably from 0 to 0.005, and even more preferably from 0 to 0.001. The value of v is preferably from 0.59 to 0.61, more preferably from 0.59 to 0.605, and even more preferably from 0.595 to 0.605. Since Zr is known to phase-separate in thermal equilibrium, the value of u in the case of performing a sufficiently long heat treatment is theoretically 0. However, after performing a heat treatment that does not reach thermal equilibrium, Zr may inevitably be present in the second iron oxide layer X2, and its value is on the order of 10 ‐6 of.

[0033] When Cr is contained in the first iron oxide layer X1 and the second iron oxide layer X2, the first iron oxide layer X1 has the composition formula Fe 1-x-y Cr x O y (However, 0 < x ≤ 0.10, 0.57 ≤ y ≤ 0.61, and 0.29 ≤ 1 - (x + y) ≤ 0.41). Here, the first iron oxide layer X1 is composed of a maghemite crystal phase. The second iron oxide layer X2 has the composition formula Fe 1-u-v Cr u O v (However, 0 ≤ u ≤ 0.01, 0.59 ≤ v ≤ 0.61, and 0.37 ≤ 1 - (u + v) ≤ 0.41).

[0034] In addition, x, y, u, and v are not limited to the above-mentioned values. The value of x is preferably 0.001 to 0.1, more preferably 0.02 to 0.05, and even more preferably 0.04 to 0.05. The value of y is preferably 0.57 to 0.61, more preferably 0.58 to 0.605, and even more preferably 0.59 to 0.605. The value of u is preferably 0 to 0.01, more preferably 0 to 0.005, and even more preferably 0 to 0.001. The value of v is preferably 0.59 to 0.61, more preferably 0.59 to 0.605, and even more preferably 0.595 to 0.605. It is known that Cr sublimes in the heat treatment described later, and therefore the value of u is theoretically 0 when the heat treatment is performed for a sufficiently long time. However, Cr may be inevitably present in the second iron oxide layer X2 even after the heat treatment is performed sufficiently, and the value of u is 10 ‐6 This is the order.

[0035] When at least two elements selected from the group consisting of Si, Mn, Zr, and Cr are contained in combination in the first iron oxide layer X1 and the second iron oxide layer X2, the total content of these elements in the first iron oxide layer X1 is preferably 0.1 to 10 at.%, more preferably 0.5 to 5 at.%, and even more preferably 0.5 to 3 at.%, and the total content of these elements in the second iron oxide layer X2 is preferably 0 to 1 at.%, more preferably 0 to 0.5 at.%, and even more preferably 0 to 0.1 at.%.

[0036] The composite iron oxide thin film according to the present invention has a saturation magnetization of preferably 1 kG or more, more preferably 3 kG or more, even more preferably 4 kG or more, and most preferably 4.5 kG or more. There is no particular upper limit for the saturation magnetization, but it may be 100 kG depending on the characteristics of the material.

[0037] The composite iron oxide thin film of the present invention has a light transmittance of preferably 60%, more preferably 70% or more, and still more preferably 80% or more with respect to incident light of any wavelength in the visible light region to the near infrared region with a wavelength of preferably 500 nm to 3200 nm, more preferably 1000 nm to 3000 nm, per 1 μm in thickness. Also, although the upper limit value of the light transmittance is 100%, it may be 98% due to the characteristics of the substance. Since it has good light transmittance in such a wide range, it is suitable for various optical communication devices and photocatalysts that respond to visible light.

[0038] In addition, in the present invention, although an embodiment of a composite iron oxide thin film was shown, among others, the compositional formula Fe 1-x-y Si x O y (However, 0 < x ≤ 0.10, 0.57 ≤ y ≤ 0.61, and 0.29 ≤ 1 - (x + y) ≤ 0.41.) and the core represented by the compositional formula Fe 1-u-v Si u O v (However, 0 ≤ u ≤ 0.01, 0.59 ≤ v ≤ 0.61, and 0.37 ≤ 1 - (u + v) ≤ 0.41.) It may have a form of composite iron oxide powder composed of a surface layer covering the surface of the core represented by.

[0039] By using the magneto-optical material according to the present invention, it becomes possible to promote the Faraday effect, leading to higher performance of the device. Also, by using a photocatalytic material, it becomes possible to efficiently photoelectrically convert visible light, leading to higher activation of the photocatalytic function. This also enables cost reduction of the device.

[0040] (Manufacturing method) A composite target in which chips of at least one element selected from the group consisting of Si, Mn, Zr, and Cr are arranged on a target of magnetite (Fe 3 O 4 ) is installed in a thin film manufacturing apparatus (such as a sputtering apparatus). As the addition concentration of at least one element selected from the group consisting of Si, Mn, Zr, and Cr, the element addition Fe 3 O 4It is preferable to adopt a concentration that maximizes the magnetization of the thin film, for example, 1.8 at.% in the case of Si (see, for example, non-patent documents 21 and 22). Then, after a substrate such as a Corning #7059 glass substrate is sputter-etched for an appropriate time, an AC voltage is applied to the target, and the Fe-doped metal is deposited in an atmosphere of Ar gas or the like. 3 O 4 A thin film is formed (see, for example, Patent Document 1 and Non-Patent Document 21). 1-a-b L a O b (wherein L is at least one element selected from the group consisting of Si, Mn, Zr and Cr), and an iron oxide morphology consisting of a magnetite crystal phase is created. At this time, the thin film is created without performing any special treatment such as applying a bias voltage near the substrate.

[0041] Next, elemental addition Fe 3 O 4 The thin film is heat-treated in air at a predetermined heat treatment temperature within a temperature range of, for example, 573 K to 873 K (300° C. to 600° C.) for a predetermined heat treatment period within a range of, for example, 10 minutes to 256 days. As a result, the surface layer of the thin film changes into a second iron oxide layer X2, and a first iron oxide layer X1 is formed on the substrate side of the surface layer and has a structure of the thin film composed of maghemite containing at least one element selected from the group consisting of Si, Mn, Zr, and Cr, thereby producing the composite iron oxide thin film of the present invention.

[0042] The heat treatment temperature is preferably 573K to 873K, more preferably 673K ​​to 873K, and even more preferably 673K ​​to 773K, from the viewpoint of preventing thermal destruction of the thin films while developing the first iron oxide thin film X1 and the second iron oxide thin film X2 by the heat treatment.

[0043] The heat treatment time is preferably 10 minutes to 256 days, more preferably 390 minutes to 256 days, and even more preferably 76,950 minutes to 63 days, from the viewpoint of preventing thermal destruction of the thin films while developing the first iron oxide thin film X1 and the second iron oxide thin film X2 by the heat treatment.

[0044] The composite iron oxide film is removed from the chamber after the interior of the chamber has been purged with a suitable gas, such as nitrogen.

[0045] First, we will explain the composite iron oxide thin film containing Si as an additive element.

[0046] Two 5 mm square Si chips were attached to the surface of a 4-inch magnetite target using double-sided carbon tape, and the target was placed in the vacuum chamber of a high-frequency sputtering device. A glass plate (manufactured by Corning) was placed in the vacuum chamber as the substrate 3. Next, the vacuum chamber was filled with 1.5×10 -7 The chamber was evacuated to a vacuum of 100 Torr, and then argon gas was supplied into the vacuum chamber to control the gas pressure to 2 mTorr while depositing the film for 60 minutes at a power input of 200 W, thereby producing the iron oxide thin film of Example 1 having a thickness of 1 μm. Analysis of the composition of the iron oxide thin film of Example 1 revealed that the amount of Si added was 2.8 at.%.

[0047] (Examples 2 to 6) Except for varying the number (or size) of Si chips attached to the surface of the magnetite target, the iron oxide thin films of Examples 2 to 6 were produced in the same manner as in Example 1. When the composition of each of the iron oxide thin films of Examples 2 to 6 was analyzed, the amount of Si added was identified as shown in Table 1.

[0048] (Comparative Example) Except for changing the chip attached to the surface of the magnetite target from Si to Mo, the iron oxide thin films of Comparative Examples 1 and 2 were produced in the same manner as in Example 1. When the composition of each of the iron oxide thin films of Comparative Examples 1 and 2 was analyzed, the amounts of addition were identified as shown in Table 1.

[0049] Table 1 shows the compositions of the iron oxide thin films of Examples 1-6 and Comparative Examples 1-2.

[0050] [Table 1]

[0051] To avoid redundancy, a description of the manufacturing method will be omitted. However, for composite iron oxide thin films to which at least one element other than Si, selected from the group consisting of Mn, Zr and Cr, was added, examples corresponding to a plurality of different amounts of addition were produced by a similar manufacturing method.

[0052] (Thin film evaluation method) The magnetization of the thin films at room temperature was measured using a vibrating sample magnetometer (Tamagawa Seisakusho). The optical properties (optical transmittance) of the thin films were measured using a UV-Vis-Infrared Spectrophotometer (Shimadzu Seisakusho). The structure of the thin films was identified using X-ray diffraction (XRD) using CuKα radiation (Rigaku). The constituent elements of the thin films and the electronic state of the elements were identified using X-ray photoelectron spectroscopy (XPS) (PHI) using a monochromated Al X-ray source. The films were observed using a scanning transmission electron microscope (STEM), high-angle annular dark-field (HAADF) STEM, and energy dispersive X-ray spectroscopy (EDX) (JEOL Ltd.) operating at 200 kV for elemental analysis of Si-K, Fe-K, and OK. Samples for cross-sectional imaging were prepared using a focused ion beam.

[0053] (Characteristics of thin iron oxide films) Figure 2 shows the Fe 3 O 4 and SiFe 2 O 4The square points corresponding to each composition are shown. In addition, in Fig. 2, the composition analysis results of the Si-added iron oxide thin film in the film-formed state (before heat treatment) are shown with black circles. In Fig. 2, the dashed line indicates the ratio of Si to Fe. 3 O 4 The composition (Si+Fe 2 O 3 The dashed double-dashed line represents the Si and Fe 3 O 4 The composition assumed to be solid-soluble (Fe 3 O 4 and SiFe 2 O 4 The analysis results show that the change is along the line assuming a solid solution, rather than along the line assuming phase separation. 3 O 4 The reason why the amount of Si added to the iron oxide thin film is set to 0.1 or less (10 at.%) in atomic ratio is that if the amount of Si added exceeds this amount, the structure changes rapidly, making it difficult for Si to dissolve in magnetite, and the film becomes amorphous.

[0054] Although the explanation is omitted to avoid redundancy, the analysis results for Zr, Mn and Cr are similar, and the added elements are 3 O 4 From the viewpoint of dissolving the additive element in magnetite, it is preferable to adjust the amount of addition. From the viewpoint of reliably dissolving the additive element in magnetite, when the additive element in the dissolved iron oxide thin film is Zr, the amount of addition is preferably 0.1 or less (10 at.% or less) in atomic ratio, when the additive element in the dissolved iron oxide thin film is Mn, the amount of addition is preferably 0.22 or less (22 at.% or less) in atomic ratio, and when the additive element in the dissolved iron oxide thin film is Cr, the amount of addition is preferably 0.1 or less (10 at.% or less) in atomic ratio. If the amount of addition is exceeded, the structure changes rapidly, the element becomes difficult to dissolve in magnetite, and the magnetite becomes amorphous.

[0055] FIG. 3A shows the correlation between the amount of Si added and the X-ray diffraction pattern of the iron oxide thin film before heat treatment in the film-formed state (before heat treatment). When the amount of Si added is 0 [at.%] (x = 0), a small peak is observed at Miller index (104) corresponding to the corundum structure. When the amount of Si added is 0.7 [at.%] (x = 0.049) or more, no peak corresponding to the corundum structure is observed, and only peaks are observed at Miller indexes (311), (222), (422), and (511) corresponding to the inverse spinel structure specific to magnetite. When the amount of Si added is 7.8 [at.%] (x = 0.546), no peak corresponding to the inverse spinel structure is observed. That is, when the amount of Si added is 0 [at.%] (x = 0), a mixed phase of magnetite and hematite is formed, when even a trace amount of Si is added, a single phase of magnetite is formed, and when the amount of Si added exceeds a certain value, amorphous phase is formed.

[0056] FIG. 3B shows the magnetization-magnetic field curves of the iron oxide thin film before heat treatment and the amount of Si added in the formed state (before heat treatment). When the amount of Si added was 0 [at.%] and when the amount of Si added was 2.8 [at.%], the first iron oxide layer X1 exhibited ferrimagnetic behavior. When the amount of Si added was 2.8 [at.%], the ferrimagnetic behavior of the iron oxide thin film was such that the saturation magnetization was increased compared to when the amount of Si added was 0 [at.%], indicating that by adding Si, magnetite was formed as a single phase and high magnetization was obtained (saturation magnetization was increased from less than 4 kG to 4 kG or more). On the other hand, when the amount of Si added exceeded a certain value, amorphous phase was formed, and the ferrimagnetic behavior was no longer exhibited.

[0057] FIG. 4A shows the magnetization at 10 kOe as a function of the amount of Si added to the iron oxide thin film in the film-formed state (before heat treatment). Referring to FIG. 4A, in the relatively low concentration region, the magnetization of the iron oxide shows a tendency to increase with increasing amount of Si added, but when the amount of Si added exceeds a certain value, it decreases rapidly, and thereafter the magnetization has a low value. Here, the mixture of hematite and magnetite in the initial state is different between the disk A and the disk B, which are the sputtering targets. Therefore, it is presumed that the values ​​of the curves for disk A and disk B in FIG. 4A are different. On the other hand, since the magnetization was maximized when the amount of Si added in disk B was 1.8 [at.%], it was presumed that the magnetization was maximized when the amount of Si added was around 1.8 [at.%].

[0058] Here, the predetermined amount is preferably 0.5 to 3.5 [at.%], more preferably 0.5 to 2.5 [at.%], and even more preferably 1.5 to 2.5 [at.%] when the additive element is Si. Also, referring to FIG. 10B described later, when the additive element is Zr, the predetermined amount is preferably 0.5 to 3.5 [at.%], more preferably 1.2 to 3.2 [at.%], and even more preferably 1.7 to 2.7 [at.%]. Also, referring to FIG. 10C described later, when the additive element is Mn, the predetermined amount is preferably 7.5 to 10.5 [at.%], more preferably 8.0 to 10 [at.%], and even more preferably 8.5 to 9.5 [at.%]. Also, referring to FIG. 10D described later, when the added element is Cr, the predetermined amount is preferably 1.5 to 5.0 [at.%], more preferably 2.0 to 5.0 [at.%], and even more preferably 4.0 to 5.0 [at.%].

[0059] By setting the additive element to the above value, the additive element is Fe 3 O 4When the amount of the added element is less than the above numerical value or when the added element is not added, the magnetization does not become larger than necessary, and when the amount of the added element is more than the above numerical value, the added element is less likely to be solid-dissolved in magnetite, or the crystallinity is deteriorated or the element is easily made amorphous, or the element is transferred to a solid solution that is not magnetized, and the magnetization is reduced.

[0060] Figure 4B shows the XPS spectrum of the iron oxide thin film with 2.8 at.% Si addition in the as-formed state (before heat treatment). The peak of the XPS spectrum exists between the trivalent and tetravalent states of Si, suggesting that the Si added to the iron oxide thin film is ionized and dissolved in magnetite. This result is in good agreement with the tendency of the analysis results in the as-formed state (Figure 2).

[0061] FIG. 5A shows the X-ray diffraction pattern of the composite iron oxide thin film that was heat-treated at 673K ​​for 256 days. The figure shown in FIG. 5A shows an embodiment in which the amount of Si added is 2.8 [at.%]. In the composite iron oxide after heat treatment, small peaks are observed at Miller indices (012) and (104) corresponding to the corundum structure. In addition, peaks are observed at Miller indices (220), (311), (422), and (511) corresponding to the spinel structure, and the peak at Miller index (311) is particularly large. This is due to the first iron oxide layer X1 having a spinel structure and the second iron oxide X2 having a corundum structure.

[0062] FIG. 5B shows the Raman spectrum of the composite iron oxide thin film that was heat-treated at 673K ​​for 256 days. The figure shown in FIG. 5B shows an embodiment in which the amount of Si added is 2.8 [at.%]. In addition to the peak corresponding to hematite, the Raman spectrum also shows a peak corresponding to maghemite, which makes it clear that the spinel structure in FIG. 5A is maghemite. That is, it was revealed that the iron oxide mainly composed of magnetite in the film-formed state is oxidized by heat treatment, and the surface changes to a second iron oxide layer X2 mainly composed of hematite, and the inside undergoes a phase transition to a first iron oxide layer X1 mainly composed of maghemite.

[0063] (Microstructure of Complex Iron Oxide Thin Films) The microstructure of the Si-doped complex iron oxide thin film was examined to investigate the morphology of the phase mixture formed during the heat treatment process. Figure 6A shows a HAADF-STEM image of a complex iron oxide thin film (Si doping amount is 2.8 at.%) that was heat-treated in air at 673 K for 256 days. In the surface layer (second iron oxide layer X2), Fe (see Fig. 6D; STEM-EDX elemental map image of Fe-K) and O (see Fig. 6C; STEM-EDX elemental map image of OK) are distributed throughout, while Si is almost absent (see Fig. 6B; STEM-EDX elemental map image of Si-K), and the surface morphology shows an irregular structure.

[0064] FIG. 7A shows a cross-sectional STEM image of a composite iron oxide thin film (Si doping amount is 2.8 at.%) that was heat-treated at a temperature of 673 K for 256 days. Two different morphologies were confirmed: (1) a rough structure (random structure) in the surface layer (second iron oxide layer X2), and (2) a columnar structure in the first iron oxide layer X1 located on the substrate side of the surface layer. FIG. 7B shows the result of fast Fourier transform analysis of the lattice image of the surface layer. Each lattice plane and the interplanar spacing are consistent with hematite. FIG. 7C shows the result of fast Fourier transform analysis of the lattice image of the internal columnar structure. Each lattice plane and the interplanar spacing are consistent with maghemite. Thus, a heterostructure of hematite constituting the second iron oxide layer X2 as the surface layer of the composite iron oxide thin film and Si-containing maghemite constituting the first iron oxide layer X1 was generated by the heat treatment.

[0065] To avoid redundancy, a detailed explanation of the structure of the composite iron oxide thin film is omitted here. However, it was suggested that similar structural characteristics were observed in a composite iron oxide thin film to which at least one element other than Si, selected from the group consisting of Mn, Zr, and Cr, was added.

[0066] (Magnetization of Complex Iron Oxide Thin Films) FIG. 8A shows the relationship between the magnetization and heat treatment time of an iron oxide thin film (Si content: 2.8 at.%) (Example 1) when heat-treated in air at 673 K. For comparison, a sample with no additives, Fe 3 O 4 The magnetization of the thin film (Comparative Example 1) and the iron oxide thin film (Comparative Example 2) in which the additive element was changed from Si to Mo (Mo content: 1.3 at.%) in the above-mentioned structure are shown. 3 O 4 The magnetization of the film decreased rapidly, and within one day, the α-Fe 2 O 3A phase transition occurred. In the composite iron oxide thin film (Si content 2.8 at.%), a relatively large magnetization was maintained even after 258 days of heat treatment in air. In addition, the magnetization value of the composite iron oxide thin film (Si content 2.8 at.%) (Example 1) was about twice as large as that of the composite iron oxide thin film (Mo content 1.3 at.%) after about 300 days of heat treatment.

[0067] FIG. 8B shows the relationship between the magnetization of the Zr-containing iron oxide thin film and the heat treatment time when heat-treated in air at 673 K. For comparison, the magnetization of the undoped Fe 3 O 4 The magnetization of the thin film (Comparative Example 1) is shown. 3 O 4 The magnetization of the thin film decreased rapidly with the heat treatment time, and after one day of heat treatment, the α-Fe 2 O 3 The composite iron oxide thin film (Zr content: 2.2 at.%) maintained a relatively large magnetization even after 200 days of heat treatment in air. The magnetization value of the composite iron oxide thin film (Zr content: 2.2 at.%) was approximately twice as large as that of the composite iron oxide thin film (Mo content: 1.3 at.%, see Fig. 8A) after approximately 200 days of heat treatment.

[0068] FIG. 8C shows the relationship between the magnetization of the Mn-containing iron oxide thin film and the heat treatment time when the thin film is heat-treated in air at 673 K. For comparison, the magnetization of the thin film of undoped Fe 3 O 4 The magnetization of the thin film (Comparative Example 1) is shown. 3 O 4 The magnetization of the thin film decreased rapidly with the heat treatment time, and after one day of heat treatment, the α-Fe 2 O 3 The composite iron oxide thin film (Mn content 8.9 at.%) maintained a relatively large magnetization even after 200 days of heat treatment in air. The magnetization value of the composite iron oxide thin film (Mn content 8.9 at.%) was approximately twice as large as that of the composite iron oxide thin film (Mo content 1.3 at.%, see Figure 8A) after approximately 200 days of heat treatment.

[0069] Figure 8D shows the relationship between the magnetization of the Cr-containing iron oxide thin film and the heat treatment time when heat-treated in air at 673 K. In the composite iron oxide thin film (Cr content 4.5 at.%), the magnetization decreases after about 200 days of heat treatment in air, whereas a relatively large magnetization is maintained within the range of a relatively short heat treatment time (about 1 day).

[0070] The change in magnetization is the same as that of the undoped Fe 3 O 4 The results are significantly different from those of the thin film (Comparative Example 1), and show that the composite iron oxide thin films to which at least one element selected from the group consisting of Si, Zr, and Mn has been added have high oxidation resistance. Furthermore, the magnetization values ​​of these composite iron oxide thin films are greater than those of the Mo-added composite iron oxide thin film (Mo content: 1.3 at.%) (Comparative Example 2). In other words, the composite iron oxide thin films to which at least one element selected from the group consisting of Si, Zr, and Mn has been added have higher magnetization and are of higher quality than conventional composite iron oxide thin films.

[0071] FIG. 9 shows the magnetization of the composite iron oxide thin film as a function of the amount of added Si when heat-treated in air for 90 minutes at different temperatures. At all temperatures, the magnetization increases with increasing amount of added Si when the amount of added Si is relatively low (between 1 and 4 at.%), and decreases gradually when the amount of added Si is exceeded. Thereafter, the magnetization increases again with increasing heat treatment temperature and amount of added Si. Furthermore, in the absence of additives, the magnetization decreases rapidly with increasing heat treatment temperature, whereas with the addition of Si, the decrease in magnetization is suppressed even at a heat treatment temperature of 500°C, and the magnetization tends to increase, especially at relatively high concentrations of added Si.

[0072] Figure 10A shows the change in magnetization of the composite iron oxide thin film with respect to the amount of Si added at different heat treatment times in air at 673K. In the thin film without added Si, the magnetization rapidly decreases with the passage of heat treatment time, whereas the composite iron oxide thin film with added Si shows a tendency to retain the magnetization even after heat treatment, and the composite iron oxide thin film has excellent oxidation resistance. When the amount of added Si exceeds a predetermined value of 6 at.%, the magnetization of the composite iron oxide thin film shows a tendency to increase with the passage of heat treatment time. This is because the structure, which was poorly crystalline or amorphous in the deposited state, crystallizes by heat treatment, forming a maghemite phase.

[0073] Figure 10B shows the change in magnetization of the composite iron oxide thin film with different amounts of Zr added at different heat treatment times in air at 673K. As with the composite iron oxide thin film with Si added, the magnetization of the thin film without Zr added decreases rapidly with the passage of heat treatment time, whereas the composite iron oxide thin film with Zr added shows a tendency to retain magnetization even after heat treatment, and the composite iron oxide thin film has excellent oxidation resistance. When the amount of Zr added exceeds the specified value of 2.2 at.%, the magnetization of the composite iron oxide thin film shows a tendency to increase with the passage of heat treatment time. This is because the structure, which was poorly crystalline or amorphous in the deposited state, crystallizes by heat treatment, forming a maghemite phase.

[0074] FIG. 10C shows the change in magnetization of the composite iron oxide thin film with respect to the amount of Mn added at different heat treatment times in air at 673K. In the thin film without Mn added, the magnetization rapidly decreases with the passage of heat treatment time, whereas the composite iron oxide thin film with a specified amount of Mn added shows a tendency to retain the magnetization even after heat treatment, and the composite iron oxide thin film has excellent oxidation resistance. Depending on the amount of Mn added, the magnetization of the composite iron oxide thin film shows a tendency to increase or decrease with the passage of heat treatment time. In particular, when the amount of Mn added exceeds a specified value of 13 at.%, the magnetization of the composite iron oxide thin film shows a tendency to increase with the passage of heat treatment time. This is because the magnetization of magnetite almost disappears due to the high concentration of Mn in the film formation state, but manganese oxide and hematite appear and a maghemite phase is formed by heat treatment. On the other hand, when the amount of Mn added was below the prescribed value of 13 at.%, the magnetization of the composite iron oxide thin film tended to change in a complex manner with the passage of heat treatment time. This is because the structure, which had deteriorated in crystallinity or was amorphous in the deposited state, crystallized during heat treatment, forming a system in which the maghemite phase and manganese oxide phase were in solid solution.

[0075] FIG. 10D shows the change in magnetization of the composite iron oxide thin film with respect to the amount of Cr added, with different heat treatment times in air at 673 K. Similar to the composite iron oxide thin film with Si added, the composite iron oxide thin film with Cr added showed a tendency to retain magnetization even after heat treatment, and the composite iron oxide thin film has excellent oxidation resistance. When the amount of Cr added exceeded the predetermined value of 4.0 at.%, the magnetization of the composite iron oxide thin film showed a tendency to increase with the passage of heat treatment time. This is because the structure, which had deteriorated crystallinity or was amorphous in the deposited state, crystallized by heat treatment, forming a maghemite phase.

[0076] (Translucency of composite iron oxide thin films) Table 2 shows the heat treatment conditions and wavelengths for each sample, as well as the light transmittance per 1 μm thickness at 1000 [nm], 1500 [nm], 2000 [nm], 2500 [nm], and 3000 [nm].

[0077] [Table 2]

[0078] Fig. 11 shows the light transmission spectra of the composite iron oxide thin films of Example 1 and Comparative Example 2, which were subjected to heat treatment at 673 K for 256 days. As can be seen from Fig. 11, in the range from visible light to infrared light (wavelengths of 500 to 3000 nm), the light transmittance of Example 1 was shown to be improved compared to the light transmittance of Comparative Example 2. In particular, it was confirmed that the light transmittance exceeded 80% (fabricated film thickness: 1 µm) in a part of the wavelength band ranging from 600 nm to 2500 nm.

[0079] Fig. 12 shows the optical transmission spectra of the composite iron oxide thin film of Example 1 after 90 minutes of heat treatment at different temperatures. As can be seen from Fig. 12, it is suggested that the optical transmittance is improved in a relatively short time by performing heat treatment at a relatively high temperature (773K) rather than at a relatively low temperature (673K and 573K). Fig. 13A shows the optical transmission spectra of the composite iron oxide thin film of Example 1 when the heat treatment time was changed at 773K. Although not shown, the composite iron oxide thin film doped with Zr, Mn or Cr also showed the same tendency as the composite iron oxide thin film doped with Si, as will be described below.

[0080] As can be seen from Fig. 13A, the Si-doped composite iron oxide thin film reaches saturation of optical transmittance from visible to infrared at a heat treatment time of 2070 minutes. In other words, by increasing the heat treatment temperature from 673 K (Fig. 11) to 773 K, the optical transmittance reaches saturation in a relatively short heat treatment time.

[0081] Similarly, as can be seen from FIG. 13B, the composite iron oxide thin film to which Zr (content 4.0 at.%) is added has a visible to infrared light transmittance of 40 to 70% after a heat treatment time of 203 days (heat treatment temperature 673K). As can be seen from FIG. 13C and FIG. 13D, the composite iron oxide thin film to which Mn (content 8.9 at.% in FIG. 13C, content 17 at.% in FIG. 13D) is added has a visible to infrared light transmittance of over 80% at a content of 8.9 at.% and 70% at a content of 17 at.% after a heat treatment time of 113 days (heat treatment temperature 673K). As can be seen from FIG. 13E, the composite iron oxide thin film to which Cr (content 4.5 at.%) is added has a visible to infrared light transmittance of over 80% and is saturated after a heat treatment time of 203 days (heat treatment temperature 673K). That is, for any added element, the light transmittance increases with a short heat treatment time compared to the case of Mo addition. In particular, the light transmittance of the composite iron oxide thin film doped with Cr (content 4.5 at.%) increases with an extremely short heat treatment time compared to the composite iron oxide thin film doped with Mo. Furthermore, as with the composite iron oxide thin film doped with Si, the light transmittance saturates with a relatively short heat treatment time by increasing the heat treatment temperature.

[0082] In particular, referring to FIG. 13E, the light transmittance is nearly saturated after 23 days of heat treatment, and thereafter, no significant change occurs up to 203 days of heat treatment. This suggests that the phase transition from magnetite to maghemite is nearly complete after 23 days of heat treatment. On the other hand, in the example in FIG. 11 in which Mo was added, the light transmittance is relatively low even after 256 days of heat treatment, and it is presumed that the phase transition from magnetite to maghemite is in a transitional region. In other words, compared to the addition of Mo, the addition of Cr clearly has the effect of causing a rapid phase transition to maghemite.

[0083] Therefore, as a result of the above, the optical transmittance and saturation magnetization are improved, and therefore, when the composite iron oxide thin film is used, for example, as a magneto-optical element, the optical transmittance hardly decreases even if the film is made thick, making it possible to provide a desired Faraday rotation angle. Therefore, the composite iron oxide thin film of the present invention is expected to improve the performance of the device. Furthermore, when used as a photocatalyst, the heterojunction of the hematite in the surface layer and the maghemite in the internal layer is expected to achieve high activation by visible light. Furthermore, in the region where the amount of Si added exceeds 6 at.%, SiFe 2 O 4 (See Figure 2) SiFe 2 O 4 is a semiconductor that absorbs ultraviolet light, and is expected to be effective as a highly active photocatalyst covering the range from ultraviolet to visible light due to the heterojunction with hematite in the surface layer. These effects are brought about by the fact that the composite iron oxide thin film of the present invention has been improved in any one of oxidation resistance, magnetization, and light transmittance compared to conventional films.

[0084] (Method of manufacturing composite iron oxide powder) Next, the composition formula Fe 1-x-y S x O y Maghemite (γ-Fe 2 O 3 ) crystal layers and the composition formula Fe 1-u-v S u O v Hematite (α-Fe 2 O 3 The following describes a method for producing a composite iron oxide powder having a form constituted by a surface layer covering the surface of an inner core constituted by a crystalline phase. Note that x, y, u and v preferably have the same numerical ranges as those of the composite iron oxide thin film described above.

[0085] As shown in Figure 14, α-Fe 2 O 3 , α-Fe and SiO 2The mixed powder or granules derived from the mixed powder were mixed in a mortar and pressed into a disk shape, and the pressed compact was heat-treated in a non-oxidizing atmosphere or in a vacuum at a temperature in the range of 1073 to 1473 K for a time in the range of 4 to 48 hours to produce a sintered body by sintering the composite iron oxide powder. The heat-treated press compact was then re-pulverized to produce a composite iron oxide powder according to one embodiment of the present invention.

[0086] In normal press molding, a compact (about 1 g) containing a small amount of powder is produced. Instead of press molding, hot press molding may be performed in a disk shape at a temperature in the temperature range of 1123 to 1223 for a time in the time range of 3 to 30 minutes. In this way, a large amount of powder compacts (about 200 g) can be produced at one time, and a large amount of composite iron oxide powder can be produced. Note that, while encapsulation is performed in normal press molding, encapsulation may be omitted in hot press molding, and heat treatment may be performed directly.

[0087] (Structural characteristics of composite iron oxide powder) In Fig. 15, Si x Fe 3-x O 4 The relationship between the magnetization of the powder and the composition x is shown. The magnetization was measured in the sintered state. x Fe 3-x O 4 The powder was shown to be ferromagnetic in all compositions where x was 0.5 or less. x Fe 3-x O 4 The powder suggests that the ferromagnetism of magnetite is dominant. x Fe 3-x O 4 The powder showed a gradual decrease with increasing Si concentration. x Fe 3-x O 4 The sintered body composed of the powder was pulverized to produce a composite iron oxide powder.

[0088] FIG. 16 shows the Si composition x (Si x Fe 3-x O 4 The correlation between the X-ray diffraction patterns of the composite iron oxide powder and the amount of Fe in the powder is shown. 3 O 4 For compositions of x = 0.15 or more, only the diffraction peak from SiO 2 Diffraction peaks from Fe with Si in solid solution are also observed up to x = 0.1. 3 O 4 At x = 0.15 or more, the solid solution and SiO 2 This is a two-phase coexistence state.

[0089] Figure 17 shows the Raman spectra of the composite iron oxide powder with x=0.1 before and after heat treatment. The Raman spectrum after heat treatment contains a peak corresponding to maghemite in addition to a peak corresponding to hematite, which makes it clear that the spinel structure in Figure 16 is maghemite. In other words, it was made clear that the iron oxide mainly composed of magnetite in the powder state is oxidized by heat treatment, the surface layer changes to iron oxide mainly composed of hematite, and the inner core undergoes a phase transition to an iron oxide layer mainly composed of maghemite.

[0090] Moreover, as is clear from the fact that these composite iron oxide powders have an inner core corresponding to the first iron oxide layer X1 of the composite iron oxide thin film and a surface layer corresponding to the second iron oxide layer X2, they have the same physical properties as the composite iron oxide thin film described above. Therefore, explanations of the magnetic properties and optical properties will be omitted to avoid redundancy. [Explanation of symbols]

[0091] X1: First iron oxide layer, X2: Second iron oxide layer.

Claims

1. Composition formula Fe 1-x-y S x O y (wherein 0<x≦0.10, 0.57≦y≦0.61, and 0.29≦1−(x+y)≦0.41) and a first iron oxide layer constituted by a maghemite crystal phase; Composition formula Fe 1-u-v S u O v (wherein 0≦u≦0.01, 0.59≦v≦0.61, and 0.37≦1-(u+v)≦0.41) and the composite iron oxide thin film is composed of a hematite crystal phase, and further comprises a second iron oxide layer as a surface layer forming a heterostructure with the first iron oxide layer.

2. Composition formula Fe 1-x-y Zr x O y (wherein 0<x≦0.10, 0.57≦y≦0.61, and 0.29≦1−(x+y)≦0.41) and a first iron oxide layer constituted by a maghemite crystal phase; Composition formula Fe 1-u-v Zr u O v (wherein 0≦u≦0.01, 0.59≦v≦0.61, and 0.37≦1-(u+v)≦0.41) and the composite iron oxide thin film is composed of a hematite crystal phase, and further comprises a second iron oxide layer as a surface layer forming a heterostructure with the first iron oxide layer.

3. Composition formula Fe 1-x-y Mn x O y (wherein 0<x≦0.22, 0.57≦y≦0.61, and 0.29≦1−(x+y)≦0.41) and a first iron oxide layer constituted by a maghemite crystal phase; Composition formula Fe 1-u-v Mn u O v (wherein 0≦u≦0.01, 0.59≦v≦0.61, and 0.37≦1-(u+v)≦0.41) and the composite iron oxide thin film is composed of a hematite crystal phase, and further comprises a second iron oxide layer as a surface layer forming a heterostructure with the first iron oxide layer.

4. Composition formula Fe 1-x-y Cr x O y (wherein 0<x≦0.10, 0.57≦y≦0.61, and 0.29≦1−(x+y)≦0.41) and a first iron oxide layer constituted by a maghemite crystal phase; Composition formula Fe 1-u-v Cr u O v (wherein 0≦u≦0.01, 0.59≦v≦0.61, and 0.37≦1-(u+v)≦0.41) and the composite iron oxide thin film is composed of a hematite crystal phase, and further comprises a second iron oxide layer as a surface layer forming a heterostructure with the first iron oxide layer.

5. Fe as the target material 3 O 4 A composite target with Si chips placed on the target was used to deposit Fe with the composition formula Fe1, Fe2, Fe3, Fe4, Fe5, Fe6, Fe7, Fe8, Fe9, Fe10, Fe11, Fe12, Fe13, Fe14, Fe15, Fe16, Fe17, Fe18, Fe19, Fe20, Fe15, Fe21, Fe16, Fe18, Fe22, Fe15, Fe16, Fe17, Fe23, 1-a-b S a O b (wherein 0<a≦0.1, 0.48≦b≦0.61, and 0.32≦1−(a+b)≦0.43) and a thin film constituted by a magnetite crystal phase; The thin film is heat-treated at a predetermined temperature in the range of 573K to 873K (300°C to 600°C) for a predetermined time in the range of 10 minutes to 256 days, thereby forming a surface layer of the thin film having the composition formula Fe 1-u-v S u O v (wherein 0≦u≦0.01, 0.59≦v≦0.61, and 0.37≦1−(u+v)≦0.41) and a surface layer constituted by a hematite crystal phase is prepared, and an inner layer of the thin film is formed of a composition formula Fe 1-x-y S x O y (wherein 0<x≦0.10, 0.57≦y≦0.61, and 0.29≦1-(x+y)≦0.41), and forming an inner layer constituted by a maghemite crystal phase.

6. Fe as the target material 3 O 4 A composite target with Zr chips placed on the target was used for radio frequency sputtering to produce a compound with the formula Fe 1-a-b Zr a O b (wherein 0<a≦0.1, 0.48≦b≦0.61, and 0.32≦1−(a+b)≦0.43) and a thin film constituted by a magnetite crystal phase; The thin film is heat-treated at a predetermined temperature in the range of 573K to 873K (300°C to 600°C) for a predetermined time in the range of 10 minutes to 256 days, thereby forming a surface layer of the thin film having the composition formula Fe 1-u-v Zr u O v (wherein 0≦u≦0.01, 0.59≦v≦0.61, and 0.37≦1−(u+v)≦0.41) and a surface layer constituted by a hematite crystal phase is prepared, and an inner layer of the thin film is formed of a composition formula Fe 1-x-y Zr x O y (wherein 0<x≦0.10, 0.57≦y≦0.61, and 0.29≦1-(x+y)≦0.41), and forming an inner layer constituted by a maghemite crystal phase.

7. Fe as the target material 3 O 4 A composite target with Mn chips placed on the target was used to deposit Fe with the composition formula Fe1, Fe2, Fe3, Fe4, Fe5, Fe6, Fe7, Fe8, Fe9, Fe10, Fe11, Fe12, Fe13, Fe14, Fe15, Fe16, Fe17, Fe18, Fe19, Fe20, Fe15, Fe21, Fe16, Fe18, Fe15, Fe22, Fe15, Fe16, Fe17 1-a-b Mn a O b (wherein 0<a≦0.22, 0.48≦b≦0.61, and 0.32≦1−(a+b)≦0.43) and a thin film constituted by a magnetite crystal phase; The thin film is heat-treated at a predetermined temperature in the range of 573K to 873K (300°C to 600°C) for a predetermined time in the range of 10 minutes to 256 days, thereby forming a surface layer of the thin film having the composition formula Fe 1-u-v Mn u O v (wherein 0≦u≦0.01, 0.59≦v≦0.61, and 0.37≦1−(u+v)≦0.41) and a surface layer constituted by a hematite crystal phase is prepared, and an inner layer of the thin film is formed of a composition formula Fe 1-x-y Mn x O y (wherein 0<x≦0.22, 0.57≦y≦0.61, and 0.29≦1-(x+y)≦0.41), and forming an inner layer constituted by a maghemite crystal phase.

8. Fe as the target material 3 O 4 A composite target with Cr chips on the target was used for radio frequency sputtering to produce a compound Fe 1-a-b Cr a O b (wherein 0<a≦0.1, 0.48≦b≦0.61, and 0.32≦1−(a+b)≦0.43) and a thin film constituted by a magnetite crystal phase; The thin film is heat-treated at a predetermined temperature in the range of 573K to 873K (300°C to 600°C) for a predetermined time in the range of 10 minutes to 256 days, thereby forming a surface layer of the thin film having the composition formula Fe 1-u-v Cr u O v (wherein 0≦u≦0.01, 0.59≦v≦0.61, and 0.37≦1−(u+v)≦0.41) and a surface layer constituted by a hematite crystal phase is prepared, and an inner layer of the thin film is formed of a composition formula Fe 1-x-y Cr x O y (wherein 0<x≦0.10, 0.57≦y≦0.61, and 0.29≦1-(x+y)≦0.41), and forming an inner layer constituted by a maghemite crystal phase.

9. Composition formula Fe 1-x-y S x O y (wherein 0<x≦0.10, 0.57≦y≦0.61, and 0.29≦1−(x+y)≦0.41); Composition formula Fe 1-u-v S u O v (wherein 0≦u≦0.01, 0.59≦v≦0.61, and 0.37≦1−(u+v)≦0.41), A composite iron oxide powder, wherein a surface layer portion of the composite iron oxide powder is constituted by the hematite crystal phase, and an interior portion of the composite iron oxide powder that is at least partially covered by the surface layer portion is constituted by the maghemite crystal phase.

10. Composition formula Fe 1-x-y S x O y (wherein 0<x≦0.10, 0.57≦y≦0.61, and 0.29≦1−(x+y)≦0.41) and a maghemite crystal phase represented by the composition formula Fe 1-u-v S u O v (wherein 0≦u≦0.01, 0.59≦v≦0.61, and 0.37≦1−(u+v)≦0.41), In a non-oxidizing atmosphere or in a vacuum, at a temperature in the range of 1073 to 1473 K for a time in the range of 4 to 48 hours, 2 O 3 , α-Fe and SiO 2 A step of heat treating a compact constituted by the mixed powder; and pulverizing the heat-treated molded body.

Citation Information

Patent Citations

  • Roll electrode for hermetic sealing of semiconductor device

    JP1978089370A

  • Composite iron oxide thin film and method for producing the same

    JP7153555B2